Larval dispersal in Chrysomya megacephala, Chrysomya putoria and Cochliomyia macellaria (Dipt., Calliphoridae): Ecological implications of aggregation behaviour - Godoy, W. A C [UNESP]; Von Zuben, C. J. [UNESP]; Dos Reis, S. F. (Wiley, 1996)
In this study we investigate aggregated patterns as a consequence of post-feeding larval dispersal in three blowfly species, based on the frequency distribution of sampling units in the substrate having 0, 1, 2,..., n pupae. Statistical analysis revealed that aggregated patterns of distribution emerge as a consequence of larval dispersal, and Cochliomyia macellaria has higher levels of aggregation when compared to Chrysomya megacephala and C. putoria. Aggregation during dispersal is associated with a spatial pattern where most larvae in the species tend to pupariate near the food source. The possible consequences for the population ecology of these species are discussed.
Keywords: Chrysomya megacephala; Chrysomya putoria; Cochliomyia macellaria